Working Condition Analysis Method of the Gear Pair of Recirculating Ball Variable Ratio Steering - Ke Shanle; Gu Zhiqiang; Niu Ziru; Li Gangyan (Jixie chuandong)
In order to reflect the actual working conditions of the gear pair in the steering gear accurately,the mathematical model of the steering system is established,and the calculating formulas of the pitman arm moment and the steering nut displacement are given. A calculation method for the actual working condition of the gear pair in the circulating ball variable transmission ratio steering is proposed. Base on the vehicle steering portability test,the actual steering condition of the gear pair in a certain type of recirculating ball variable ratio is calculated,and the results is verified by simulation. The calculation result of the actual working condition of the variable transmission ratio gear is applied to the finite element analysis which can prove the feasibility of this method. The calculation method provides a loading basis for simulation and test which is closer to the reality.